STUDIES ON THE MECHANISM OF ACETATE OXIDATION BY BACTERIA : V. EVIDENCE FOR THE PARTICIPATION OF FUMARATE, MALATE, AND OXALACETATE IN THE OXIDATION OF ACETIC ACID BY ESCHERICHIA COLI - Ajl, Samuel J. (The Rockefeller University Press, 1951)
1. Simultaneous oxidation of C(14)-methyl-labeled acetate, and unlabeled malate or fumarate and α-ketoglutarate results in entrapment of labeled carbon in the C(4)-dicarboxylic acids, but not in α-ketoglutarate, although all substrates are utilized at comparable rates. 2. A large endogenous reduction of all C(4)-dicarboxylic acids (fumarate, oxalacetate, and malate) to succinate is observed under aerobic conditions, and when vigorous oxidation is proceeding. This effect occurs with both freshly harvested young (18 hour) cells and stored (2 week) cells. 3. This reduction can be considerably minimized under high oxygen tensions. 4. The quantitative concordance of these results with a Thunberg-Knoop cyclic mechanism for acetate oxidation is shown. Possible alternative C(4) products formed prior to succinate are not completely excluded, but it appears that the cells can utilize the succinate condensation as a major pathway in acetate oxidation.